Physicomechanical and magnetic properties of neoprene based rubber ferrite composites - Prema, K. H.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Polymer-Plastics Technology and Engineering, 2008)
Fine (approximately 18nm) particles of nickel ferrite were synthesized by the sol-gel technique, and their structural properties were evaluated by X-ray diffraction. Neoprene-based rubber ferrite composites were prepared by incorporating these nickel ferrite powders in the rubber matrix according to a specific recipe. The cure characteristics were analyzed, and the samples were molded into particular shapes whose properties were determined according to ASTM standards. Magnetization studies were carried out using a Vibrating Sample Magnetometer. This study indicates that neoprene rubber-based flexible magnets with desired magnetic properties and appropriate mechanical properties can be prepared by incorporating an adequate amount of nanoscale nickel ferrite particles within the rubber matrix.
Keywords: Ferrite; ferrite composites; flexible magnets; neoprene rubber; rubber; Sol-gel method

Effect of nickel nanofillers on the dielectric and magnetic properties of composites based on rubber in the X-band - Jamal, E. Muhammad Abdul; Mohanan, P.; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Applied Physics A-Materials Science & Processing, 2009)
Nickel-rubber nanocomposites were synthesized by incorporating ferromagnetic nickel nanoparticles in a natural rubber as well as neoprene rubber matrix. Complex dielectric permittivity and magnetic permeability of these composites were evaluated in the X-band microwave frequencies at room temperature using cavity perturbation technique. The dielectric loss in natural rubber is smaller compared to neoprene rubber. A steady increase in the dielectric permittivity is observed with increase in the content of nickel in both the composites. The magnetic permeability exhibits a steady decrease with increase in frequency and magnetic loss shows a relaxation at 8 GHz. The suitability of these composites as microwave absorbers is modeled based on the reflection loss which is dependant on the real and imaginary components of the complex dielectric permittivity and magnetic permeability.

Synthesis of nickel-rubber nanocomposites and evaluation of their dielectric properties - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2009)
Nanocomposites based on natural rubber and nano-sized nickel were synthesized by incorporating nickel nanoparticles in a natural rubber matrix for various loadings of the filler. Structural, morphological, magnetic and mechanical properties of the composites were evaluated along with a detailed study of dielectric properties. It was found that nickel particles were uniformly distributed in the matrix without agglomeration resulting ill a magnetic nanocomposite. The elastic properties showed an improvement with increase in filler content but breaking stress and breaking strain were found to decrease. Dielectric permittivity was found to decrease with increase in frequency, and found to increase with increase in nickel loading. The decrease in permittivity with temperature is attributed to the high volume expansivity of rubber at elevated temperatures. Dielectric loss of blank rubber as well as the composites was found to increase with temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Dielectric relaxation; Interfacial polarization; Nanocomposites

Flexible microwave absorber based on nickel ferrite nanocomposite - Sunny, Vijutha; Kurian, Philip; Mohanan, P.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2010)
Flexible magnetic composite materials were prepared by incorporating precharacterized nickel ferrite nanoparticles in a natural rubber matrix. The complex dielectric permittivity and magnetic permeability of the composites were measured at different microwave frequencies using the cavity perturbation technique. A steady increase in dielectric permittivity was observed with increase in filler concentration. Maxwell-Garnett mixture equations were employed to model the effective permittivity and permeability of the composite. Reflection loss was estimated by employing the model of single layer absorber backed with a perfect conductor. Reflection loss minima of -5.9 dB at 3.2 GHz for 12 mm thick rubber ferrite composite sheet is obtained in the S-band while a loss up to -16 dB could be achieved at 9.5 GHz in the X-band. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cavity perturbation; Complex permeability; Complex permittivity; Microwave absorber; Nanocomposites; Nickel ferrite

On the magnetic and dielectric properties of nickel-neoprene nanoconaposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Chemistry and Physics, 2010)
Nickel nanocomposites were prepared by incorporating nickel nanoparticles in a neoprene matrix according to a specific recipe for various loadings of nickel particles. The dielectric properties of these composites were evaluated for different frequencies ranging from 100 kHz to 8 MHz at different temperatures from 30 degrees C to 120 degrees C. The dielectric permittivity increases with increase of nickel concentration. Increase in temperature enhances the permittivity initially, till 40 degrees C and thereafter the permittivity decreases. The dielectric loss exhibits relaxation peaks and the peaks shift to lower frequencies with increase in volume fraction of the nickel nanoparticles in the matrix. The evaluation of magnetic and dielectric properties of these composites suggests that the dielectric permittivity can be tailored by an appropriate loading of the filler using semi-empirical equations and the magnetic properties vary according to simple mixture equations. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Composite materials; dielectric properties; Elastomers; magnetic properties

On the magnetic, mechanical and rheological properties of rubber-nickel nanocomposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Polymer Bulletin, 2010)
Rubber-nickel nanocomposites were synthesized by incorporating freshly prepared nanometric nickel particles in two different matrices namely natural rubber and neoprene rubber according to specific recipes for various loadings of nano nickel and the cure characteristics of these composites were evaluated. The maximum torque values register an increase with the increase in loading of nickel in both composites and this is attributed to the non-interacting nature of nickel nanoparticles with rubber matrices. The cure time of natural rubber composites decreases with increase in the content of nickel, and in neoprene rubber cure, time increases with increase in filler content. In natural rubber, the curing reaction seems to be activated by the presence of nickel particles. The magnetization studies of the composites reveal that the magnetic properties of nickel are retained in the composite samples. The elastic modulus of natural rubber and neoprene rubber are largely improved by the incorporation of nickel particles.
Keywords: Cure characteristics; Elastic modulus; magnetic properties; Nanocomposites

Flexible microwave absorbers based on barium hexaferrite, carbon black, and nitrile rubber for 2-12 GHz applications - Vinayasree, S.; Soloman, M. A.; Sunny, Vijutha; Mohanan, P.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Applied Physics, 2014)
Flexile single layer electromagnetic wave absorbers were designed by incorporating appropriate amounts of carbon black in a nitrile butadiene rubber matrix along with an optimized amount of magnetic counterpart, namely, barium hexaferrite for applications in S, C, and X-bands. Effective dielectric permittivity and magnetic permeability were measured using cavity perturbation method in the frequency range of 2-12 GHz. The microwave absorbing characteristics of the composites were studied in the S, C, and X-bands employing a model in which an electromagnetic wave is incident normally on a metal terminated single layer. Reflection loss exceeding -20 dB is obtained for all the samples in a wide frequency range of 2-12 GHz when an appropriate absorber thickness between 5 and 9 mm is chosen. The impact of carbon black is clearly observed in the optimized composites on the mechanical strength, thickness, band width of absorption, dielectric properties, and absorptivity. (C) 2014 AIP Publishing LLC.